Analisis Hubungan Potensi dan Persepsi Masyarakat terhadap Bank Syariah di Kabupaten Tanjung Jabung Timur - Ary Dean Amri (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Islamic banks in Indonesia are currently experiencing quite rapid development. This happens because of regulatory changes that make it easier to establish and operate Islamic banks. In addition, it is possible that the Indonesian people, who are mostly Muslim, have great potential for the development of Islamic banks, one of which is in the East Tanjung Jabung Regency area which has strong Islamic traditions. This study aims to look at the potential, preferences and behavior of the people of West Tanjung Jabung Regency towards Islamic banks. The results of the study show that the people of West Tanjung Jabung Regency have considerable potential for the development of Islamic banking which can be explained through demographic and economic factors. Preferences show that the people of West Tanjung Jabung Regency have an attitude of accepting Sharia principles and products, while the behavior of the people of West Tanjung Jabung Regency shows that they are interested in saving and obtaining financing from Islamic banks.